Feeding a High-Fat Diet for a Limited Duration Increases Cancer Incidence in a Breast Cancer Model. (7th February 2023) - Imai, Toshio; Naruse, Mie; Machida, Yukino; Fujii, Gen; Mutoh, Michihiro; Ochiai, Masako; Takahashi, Mami; Nakagama, Hitoshi
Abstract: High-fat intake by young Asian women impacts the risk of breast cancer. Understanding the underlying molecular mechanisms may be essential for disease prevention in Asia as well as globally. We aimed to examine the effects of corn oil- and animal fat-based high-fat diets (32.9 and 31.4%, respectively, of fat energy ratio as compared to 12.3% in the standard diet) on mammary carcinogenesis and alterations in gene expression and epigenetic statuses in the mammary gland during the growth stages in a rat model. An increased incidence of carcinomas was observed after the cessation of high-fat feeding. In addition, rapid tumor growth and elevations in Celsr2 expression, which may be a result of DNA hypomethylation patterns in the 3′ untranslated region of the gene were noted in the animal fat group. In the human breast carcinoma cell line MCF7, a marginal decrease in cell viability was observed following the knockdown of Celsr2, suggesting that the animal fat-associated risk of cancer is partly due to the deregulation of mammary cell proliferation via non-metabolic gene functions. The present results will contribute to the development of strategies for controlling the food-associated risk of breast cancer, particularly in younger age groups.